Kemunduran dan Keruntuhan Ekonomi Muslim Pribumi di Indonesia - Herdi Sahrasad; Ma'mun Al-Barbasy (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2018)
The article describes abour business circles and the middle class of indigenous Muslims who want the duo of President Jokowi-Jusuf Kalla (Vice President), who replaces SBY-Boedino today, can firmly and quickly put an end to social crime practices, especially how to eradicate corruption, law enforcement, community empowerment, for the sake of justice, humanity, freedom, human rights, and democracy. The Muslim commu- nities want that in this reform era, Jokowi-JK program is accompanied by a "clear and clear policy of vision" that can help people out of the economic crisis, social destruction and disintegration symptoms. During the transitional period of the Habibie era, Abdurrahman Wahid, Megawati-Hamzah Haz and SBY-Boediono and Jokowi-JK today, the discourse is still "separate" from the reality of socio-economic and cultural life of the people who are suffering and depressed by multi-crisis. As a result, the politics of the current regime that relies on discourse, does not have a socio-economic machine to realize that discourse as a social idea that can be implemented in real terms by the people, and consequently only becomes "political consumption" and the commodities of the elites and the middle class are separated from social processes in the undercurrent. In this case, the government must realize that by allowing poverty and injustice to be rampant among Muslims, that is similar with waiting for the time bomb for explosions of anger and violence.